A qualitative approach to leadership effectiveness for sustainable SMEs performance - Arham, Ahmad Fadhly; Norizan, Nor Sabrena (2023)
This study presents a case study approach to gain insights into the phenomenon of consistent success within business organisations, as perceived by accomplished leaders. There were four indepth interviews conducted with entrepreneurs. These entrepreneurs were able to not only sustain but expand their businesses through difficult economic period and COVID-19. There are two stages involved in analyzing the data. The first stage involved the thematic analysis. Excerpts from the interview data were examined to identify potential themes toward leadership effectiveness. Thematic analysis identified eight key themes towards leadership effectiveness. Subsequently, during the second stage, these eight themes underwent scrutiny from experts to gather feedback, leading to necessary refinements. The study reveals that effective leadership goes beyond merely overseeing business operations; it also entails the vital responsibility of upholding employee morale in the face of challenges and unpredictable economic and social circumstances. These leaders demonstrated swift adaptability and responsiveness to the prevailing economic climate. This paper further discusses the limitations and recommendations of the study based on the findings. Through this assessment, a multitude of valuable insights and implications for leadership in the current dynamic and demanding business environment have been revealed. This research contributes to the existing body of knowledge by introducing a resilient model comprising six dimensions: adaptability, emotional intelligence, visionary capabilities, spiritual intelligence, a growth-oriented mindset, and fostering an internal ecosystem.